Female heterogamety in Madagascar chameleons (Squamata: Chamaeleonidae: Furcifer): differentiation of sex and neo-sex chromosomes - Rovatsos, Michail; Johnson Pokorná, Martina; Altmanová, Marie; Kratochvíl, Lukáš (Scientific reports, 2015)
Amniotes possess variability in sex determining mechanisms, however, this diversity is still only partially known throughout the clade and sex determining systems still remain unknown even in such a popular and distinctive lineage as chameleons (Squamata: Acrodonta: Chamaeleonidae). Here, we present evidence for female heterogamety in this group. The Malagasy giant chameleon (Furcifer oustaleti) (chromosome number 2n = 22) possesses heteromorphic Z and W sex chromosomes with heterochromatic W. The panther chameleon (Furcifer pardalis) (2n = 22 in males, 21 in females), the second most popular chameleon species in the world pet trade, exhibits a rather rare Z1Z1Z2Z2/Z1Z2W system of multiple sex chromosomes, which most likely evolved from W-autosome fusion. Notably, its neo-W chromosome is partially heterochromatic and its female-specific genetic content has expanded into the previously autosomal region. Showing clear evidence for genotypic sex determination in the panther chameleon, we resolve the long-standing question of whether or not environmental sex determination exists in this species. Together with recent findings in other reptile lineages, our work demonstrates that female heterogamety is widespread among amniotes, adding another important piece to the mosaic of knowledge on sex determination in amniotes needed to understand the evolution of this important trait.
Keywords: ženské pohlaví; karyotypizace; ještěři; pohlavní chromozomy; Sex Determination Processes; Animals; sekvence nukleotidů; Base Sequence; Haplotypes; Electron Transport Complex IV; haplotypy; Lizards; zvířata; Pigmentation; Karyotyping; Sex Chromosomes; procesy určující pohlaví; respirační komplex IV; Female; pigmentace